Amphorae from early Roman contexts: the case of Víziváros (Budapest, Hungary) - Hárshegyi, Piroska (Rei Cretariae Romanae Fautorum Acta, 2024)
The earliest settlement in Aquincum, dated to the Claudian period in the modern Víziváros (Budapest, Hungary) was studied in course of the excavations carried out by K. Kérdő (Budapest History Museum-Aquincum Museum) between 1991 and 2003. The aim of this paper is to give a preliminary assessment of the amphorae fragments which came to light on four sites very close to each other (Ganz u. 12–14., Gyorskocsi u. 26., Kacsa u. 7., Fő u. 68.).